Integrating CRISPR-Cas12a with a DNA circuit as a generic sensing platform for amplified detection of microRNA. Issue 28 (2nd July 2020) - Peng, Shuang; Tan, Zhen; Chen, Siyu; Lei, Chunyang; Nie, Zhou
Abstract : A generic sensing strategy that integrates CRISPR-Cas12a with a DNA circuit is proposed for amplified detection of microRNA. Abstract : CRISPR-based diagnostics (CRISPR-Dx) has shown great promise in molecular diagnostics, but its utility in the sensing of microRNA (miRNA) biomarkers is limited by sensitivity, cost and robustness. Here, we describe a CRISPR-Dx method for the sensitive and cost-effective detection of miRNAs by rationally integrating CRISPR-Cas12a with DNA circuits. In this work, a modular catalytic hairpin assembly (CHA) circuit is designed to convert and amplify each target into multiple programmable DNA duplexes, which serve as triggers to initiate the trans -cleavage activity of CRISPR-Cas12a for further signal amplification. Such rational integration provides a generic assay for the effectively amplified detection of miRNA biomarkers. By simply tuning the variable regions in the CHA modules, this assay achieves sub-femtomolar sensitivity for different miRNA biomarkers, which improves the detection limit of CRISPR-Dx in the analysis of miRNA by 3–4 orders of magnitude. With the usage of the proposed assay, the sensitive assessment of miR-21 levels in different cancer cell lines and clinical serum samples has been achieved, providing a generic method for the sensitive detection of miRNA biomarkers in molecular diagnosis.